2015
DOI: 10.1155/2015/642014
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanisms of Nanostructured Titania in Turbulent Reacting Flows

Abstract: Titanium dioxide (titania) is used in chemical sensors, pigments, and paints and holds promise as an antimicrobial agent. This is due to its photoinduced activity and, in nanostructured form, its high specific surface area. Particle size and surface area result from the interplay of fluid, chemical, and thermal dynamics as well as nucleation, condensation and coagulation. After nucleation, condensation, and coagulation are the dominant phenomena affecting the particle size distribution. Manufacture of nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…Comparing the results obtained with the present modified LMC-PDF method and PBSM (Hounslow et al 1988), an excellent agreement can be observed, which validates the reliability and computational efficiency of this modified LMC-PDF method. The wider PSD with increasing Re j number is also in accordance with the previous research studies by Reade and Collins (2000) and Garrick (2015), which reveals the effect of turbulence on PSD. By increasing Re j numbers, turbulence induced mixing is greatly enhanced, which leads to an enhanced coagulation process.…”
Section: Coagulation In Turbulent Flowssupporting
confidence: 91%
See 3 more Smart Citations
“…Comparing the results obtained with the present modified LMC-PDF method and PBSM (Hounslow et al 1988), an excellent agreement can be observed, which validates the reliability and computational efficiency of this modified LMC-PDF method. The wider PSD with increasing Re j number is also in accordance with the previous research studies by Reade and Collins (2000) and Garrick (2015), which reveals the effect of turbulence on PSD. By increasing Re j numbers, turbulence induced mixing is greatly enhanced, which leads to an enhanced coagulation process.…”
Section: Coagulation In Turbulent Flowssupporting
confidence: 91%
“…However, as the Re j number further increases from 4800 to 12,800, the normalized particle number density also increases when compared with Re j number of 4800 at the same axial position. These results indicate that coagulation is weakened while nucleation is enhanced when Re j number increases from 4800 to 12,800, which is consistent with the findings in Garrick (2015) that too high injection velocity causes the delay of turbulent mixing and in turn reduces coagulation rate as mentioned above.…”
Section: Coagulation and Nucleation In Turbulent Flowssupporting
confidence: 91%
See 2 more Smart Citations
“…It must be pointed that scaling up of the experimental setup could result in increase in Reynolds number and finally in higher PSH values. It can also cause an acceleration of titania particles coagulation process [45]. Therefore, further study on development of reactor construction will consider this issue.…”
Section: Two Main Chemical Pathways For Oxidation Of Ticl 4 Vapor Havmentioning
confidence: 99%